2018
DOI: 10.1123/ijspp.2017-0620
|View full text |Cite
|
Sign up to set email alerts
|

Heat Acclimation by Postexercise Hot-Water Immersion: Reduction of Thermal Strain During Morning and Afternoon Exercise-Heat Stress After Morning Hot-Water Immersion

Abstract: Morning heat acclimation by postexercise HWI induced adaptations at rest and during exercise-heat stress in the morning and midafternoon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(54 citation statements)
references
References 25 publications
7
47
0
Order By: Relevance
“…Hot water immersion studies of untrained men show successful HA by alternating days of 30-60 minutes of hot water immersion (40-44°C) with training in the heat over 2-3 weeks [66,67], hot water immersion before exercise in the heat [72], or hot water immersion after exercise in temperate conditions [68]. These studies indicate that the volume of exercise in the heat can be reduced and still produce HA adaptations on par with~5 days of HA [17], regardless of time of day [73].…”
Section: Exercise Modementioning
confidence: 84%
“…Hot water immersion studies of untrained men show successful HA by alternating days of 30-60 minutes of hot water immersion (40-44°C) with training in the heat over 2-3 weeks [66,67], hot water immersion before exercise in the heat [72], or hot water immersion after exercise in temperate conditions [68]. These studies indicate that the volume of exercise in the heat can be reduced and still produce HA adaptations on par with~5 days of HA [17], regardless of time of day [73].…”
Section: Exercise Modementioning
confidence: 84%
“…plasma volume expansion) [114]. Contrary to the notion of a fixed clock time for adaptation, it has been reported that when implementing a post-exercise HWI model for inducing HA, morning HA induced adaptations at rest and during exercise-heat stress in both the morning and mid-afternoon [96]. It was noted that adaptation to the T CORE threshold for sweating onset was similar in the morning and afternoon, this was alongside reductions in resting and exercising T CORE , HR, RPE, and TS of a similar magnitude, irrespective of the time-of-day.…”
Section: Do Athletes Need To Train In the Heat Every Day?mentioning
confidence: 98%
“…Further to chamber-based HA protocols, alternate, cheaper and more accessible methods are now acknowledged as methods for passive (e.g. hot water bath) [95][96][97][98] and active HA strategies (e.g. overdressing and restricting heat loss during routine training) [99][100][101].…”
Section: Should the Athlete Undertake Acclimatization Or Acclimation?mentioning
confidence: 99%
See 2 more Smart Citations